Improvement of Paraneoplastic Limbic Encephalitis after Systemic Treatment with Rituximab in a Patient with B-Cell Chronic Lymphocytic Leukemia. (1st August 2013) - Nogai, Hendrik; Israel-Willner, Heike; Zschenderlein, Rolf; Pezzutto, Antonio
Abstract : Limbic encephalitis is an inflammatory disease of the central nervous system characterized by diverse neurologic symptoms including mnestic disturbances, hallucinations, and seizures as well as behavioral symptoms like depression, personality changes, and acute confusional states resembling dementia. Several antibodies have been described in the pathogenesis of limbic encephalitis. It is often a paraneoplastic syndrome associated with small cell lung cancer, breast cancer, or Hodgkin's lymphoma among others. Here, we report a patient with B-cell chronic lymphocytic leukemia (B-CLL), presenting with otherwise unexplained neurologic symptoms consistent with limbic encephalitis. Despite intensive diagnostic procedures, no causing agent could be identified. Pleocytosis consisting of T cells was detected in the cerebrospinal fluid (CSF). We initiated anti-B-cell therapy with Rituximab for B-CLL with quick and durable resolution of symptoms. We speculate that disruption of interaction between autoreactive T and malignant B cells is responsible for the therapeutic effect of Rituximab.